The Influence of Organizing Sports Events on Economic Growth in Indonesia During the Endemic Transition Period - Arfah Naila Rahmah; Irwan Triadi; Handoyo Prasetyo (International Journal of Law, Crime and Justice, 2025)
This study aims to analyze the influence of organizing sports events on economic growth in Indonesia during the endemic transition period and legal regulations on sports events during the endemic transition period. Using normative juridical and normative empirical methods with a qualitative approach, this study examines relevant legal norms, such as the Indonesian Sports Law, on the influence of the country's economy in organizing sports events. Data were obtained from documentation of primary and secondary legal sources and interviews to understand the factors of economic growth through the sports industry. The results of this study indicate that the influence on economic growth through organizing sports events in Indonesia during the endemic transition period has not been fully accommodated by existing regulations. During the endemic transition period until now, the government and several sectors that work together to boost economic growth in Indonesia have not maximized the existing opportunities. However, with the weak implementation of regulations even though regulations regarding the sports industry have been written in the law. So that inappropriate implementation can hinder economic growth, as well as the occurrence of individuals who violate and damage existing facilities and the occurrence of budget efficiency in 2025 also affect the implementation of sports events. This study recommends that the government, private sector, and community collaborate to improve infrastructure evenly and maintain and build local and international appeal through the sports industry to become a source of foreign exchange for the country like developed countries.